Cost-related non-adherence to prescribed medicines among older adults: a cross-sectional analysis of a survey in 11 developed countries. Issue 1 (31st January 2017) - Morgan, Steven G; Lee, Augustine
Abstract : Objectives: To assess the effects of costs on access to medicines in 11 developed countries offering different levels of prescription drug coverage for their populations. Design: Cross-sectional study of data from the Commonwealth Fund 2014 International Health Policy Survey of Older Adults. Setting: Telephone survey conducted in 11 high-income countries: Australia, Canada, France, Germany, the Netherlands, New Zealand, Norway, Sweden, Switzerland, the UK and the USA. Participants: 22 532 adults aged 55 and older and living in the community in studied countries. Primary outcome measure: Self-reported cost-related non-adherence (CRNA) in the form of either not filling a prescription or skipping doses within the last 12 months because of out-of-pocket costs. Results: Estimated prevalence of CRNA among all older adults varied from <3% in the France, Norway, Sweden, Switzerland and the UK to 16.8% in the USA. Canada had the second highest national prevalence of CRNA (8.3%), followed by Australia (6.8%). Older adults in the USA were approximately six times more likely to report CRNA than older adults in the UK (adjusted OR=6.09; 95% CI 3.60 to 10.20). Older adults in Australia and Canada were also statistically significantly more likely to report CRNA than older adults in the UK. Across most countries, the prevalence of CRNA was higher among lower income residents and lower among residents over age 65. Conclusions: Observed differences in national prevalence of CRNA appear to follow lines of availability of prescription drug coverage and the extent of direct patient charges for prescriptions under available drug plans.